Political Economy of the Wheat Sector in Egypt: Seed Systems, Varietal Adoption, and Impacts - Bishaw, Zewdie; Yigezu, Yigezu; Azab Moustafa, Moustafa (International Center for Agricultural Research in the Dry Areas, 2024)
Wheat has been an important food staple in Egypt from time immemorial and remains one of the most (if not the single most) important food security crops in the country. Currently, wheat provides one-third (35 percent) of the typical Egyptian’s total daily calorie intake. On average, the crop represents about 10 percent of the total value of agricultural production and about 20 percent of all agricultural imports, which depicts the country’s insurmountable food security challenge.